Sequences contained within the promoter of the human thymidine kinase gene can direct cell-cycle regulation of heterologous fusion genes. - Kim, Y K (1988)
Recent evidence on the transcriptional regulation of the human thymidine kinase (TK) gene raises the possibility that cell-cycle regulatory sequences may be localized within its promoter. A hybrid gene that combines the TK 5' flanking sequence and the coding region of the bacterial neomycin-resistance gene (neo) has been constructed. Upon transfection into a hamster fibroblast cell line K12, the hybrid gene exhibits cell-cycle-dependent expression. Deletion analysis reveals that the region important for cell-cycle regulation is within -441 to -63 nucleotides from the transcriptional initiation site. This region (-441 to -63) also confers cell-cycle regulation to the herpes simplex virus thymidine kinase (HSVtk) promoter, which is not expressed in a cell-cycle manner. We conclude that the -441 to -63 sequence within the human TK promoter is important for cell-cycle-dependent expression.